KOMUNITAS SOSIAL “SIGER” DI LAMPUNG - Hiskia Given Stehan; Suwandi Supatra (Jurusan Arsitektur dan Perencanaan, 2021)
Basically, humans are not far from all kinds of things that are related to social matters, both personally and in groups, and have been around for centuries, which have been summarized or adhered to by the traditions that characterize humans in a place. However, over time, the early traditions became lost and replaced in the form of global modernization which indirectly changed the form of early social activities. Because of this shift in social activities, the relationship with the community at the top level shifted slightly because the traditional relationship also shifted. It is the problem that has arisen as a result of this shift that causes human dwelling begin to change. Therefore, the aim of this result is to fuse social problems between the community at the top level and the surrounding community with modern forms within the scope of traditions which are the source of social life. Because within the scope of the people of Lampung, the unifier of the community is the symbol of Siger which will be the center of the design results.Keyword: Dwelling; Humans; Modernization; Siger; Traditions Abstrak Manusia pada dasarnya tidak jauh dari segala macam hal yang bersangkutan pada hal sosial, baik secara personal dan kelompok, dan sudah ada sejak dari abad lama yang dirangkum atau dianut secara adat tradisi yang menjadi ciri khas manusia di suatu tempat. Namun seiring berjalannya waktu, tradisi awal menjadi menghilang tergantikan dalam bentuk modernisasi dari global yang secara tidak langsung mengganti bentuk kegiatan sosial awal. Karena adanya pergeseran kegiatan sosial tersebut, maka hubungan dengan masyarakat dengan tingkat atas sedikit bergeser karena hubungan tradisi yang juga bergeser. Masalah yang timbul akibat pergesaran inilah yang membuat bentuk berhuni manusia mulai berubah. Maka dari itu, tujuan dari hasil ini untuk melebur masalah sosial antara masyarakat dengan tingkat teratas maupun masyarakat sekitarnya dengan bentuk yang modern dalam lingkup adat tradisi yang menjadi sumber kehidupan bersosial. Karena dalam lingkup masyarakat Lampung, maka sebagai pemersatu masyarakat adalah berlambang Siger yang akan menjadi pusat dari hasil perancangan.